A perspective in development : gender focus - Haider, Raana (Dhaka, Bangladesh : University Press Limited, 1995)
In the context of developing countries.
Includes bibliographical references (pages [165]-184) and index.
BIED
Complimentary copy from BIED
Keywords: Women in development; Women -- Developing countries -- Social conditions; Women -- Developing countries -- Economics conditions